A Multivariate Approach To A Comparative Geochemical Study Within The Redmoor Sheeted-Vein Complex, East Cornwall, UK - P. S. Newall (Society for Mining, Metallurgy & Exploration, 1991)
As part of a much larger research project, factor analysis was employed to help interpret and compare the geochemical signatures produced by two different sample media; a traditional -80# soil fraction, and a coarse float. Both sample types were collected by hand auger from the extension zone of the Redmoor sheeted-vein complex and analyzed -for 19 major and trace elements. The rationale behind the study infers that the geochemical anomalies produced by wallrock alteration around such targets can be better detected in the lithogeochemical rather than the soil environment, sometimes at considerable distance from their source.